The Central Andes of Peru: a key area for the conservation of Polylepis forest biodiversity - Quispe-Melgar H.R. (2020)
Polylepis forests are threatened high Andean ecosystems that harbour unique species of flora and fauna. However, there is little information on the avifauna associated with these forests in the Central Andes of Peru. We evaluated 12 bird communities in the Junín, Lima and Huancavelica departments of Peru and recorded richness-abundance data that were used to perform an analysis of ?- and ?-diversity using Hill numbers. In addition, we built two species matrices (presence-absence data) for three previously identified key bird conservation areas and our study area, first with the species that regularly inhabit the Polylepis forests and second with the species of conservation interest. We found that the Polylepis forests of the Central Andes of Peru have a high diversity of birds. Some of these birds have a strong affinity for Polylepis forests, and another group is typical of the tree line of the Yungas. Moreover, we identified a unique set of 27 species of conservation interest in this region. Since the Central Andes of Peru also harbour three endemic species of Polylepis, it should be considered an important area for the conservation of high Andean biodiversity. © 2019, Deutsche Ornithologen-Gesellschaft e.V.